Dynamic relationships between price and net asset value for Asian real estate stocks - Kim Hiang Liow; Sherry Yeo (International Journal of Financial Studies, 2018)
This paper examines short- and long-term behavior of the price-to net asset value ratio in six Asian public real estate markets. We find mean-reverting behavior of the ratio and spillover effects, where each of the examined public real estate markets correlates with other markets. Additionally, the unexpected shock correlating with the price-to-net asset value ratio in one market has a positive or negative correlation with the ratios of other markets. Our results offer fresh insights to portfolio managers, policymakers, and academic researchers into the regional and country market dynamics of public real estate valuation and cross-country interaction from the long-term and short-term perspectives.
Keywords: 330; price-to-net asset value ratio; Asian public real estate; panel co-integration; common factors; generalized spillover index; generalized impulse response functions